Branding Produk UMKM Tempe Mendoan Cah Gombong Melalui Desain Logo dan Kemasan - Dara Julia Asmara Dita; Syamsul Huda; Anisa Fitria Utami (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this study is to assist MSME business actors in creating a brand as an effort that can be made in increasing the selling value of MSME products, namely by branding. the purpose of having a brand for products is to distinguish between one product and another, as well as to identify products so that they are different from their competitors. designing logos and packaging is an important component in branding activities. Cah Gombong Tempe Mendoan MSME located in Wonokerto Village, Wonosalam District, Jombang Regency is one of the MSMEs that does not yet have a brand for its products. The method used in the implementation of this community service is the Participatory Action Research (PAR) method. In order for Tempe Mendoan Cah Gombong MSMEs to maximize sales and introduce their products more widely, a new logo and packaging for Tempe Mendoan Cah Gombong MSME products were made